Immunological parameters of macrophages infected by methicillin resistant/sensitive Staphylococcus aureus - Natália Gomes de Morais; Thacianna Barreto da Costa; Thays Miranda de Almeida; Maiara Santos Severo; Célia Maria Machado Barbosa de Castro (Sociedade Brasileira de Patologia Clínica, 2013)
INTRODUCTION: Could changes in Staphylococcus aureus cellular walls, which are commonly associated with multidrug resistance phenotype, influence their immune evasion mechanisms? OBJECTIVE: To evaluate the microbicide response and survival of alveolar macrophages after in vitro infection with methicillin-sensitive and methicillin-resistant Staphylococcus aureus. MATERIAL AND METHODS: We used 20 adult, male, albino, Wistar rats. The alveolar macrophage samples were obtained after tracheostomy and bronchoalveolar lavage. The alveolar macrophages were cultured in the proportion of 1:1 cells/ml Roswell Park Memorial Institute (RPMI) medium/well and isolated by plate adhesion. For the assessment of immunological parameters, four systems were established: negative control, positive control, methicillin sensitive S. aureus (MSSA) and methicillin resistant S. aureus (MRSA). RESULTS: When comparing MRSA and MSSA systems, there was no significant difference as to adhesion and phagocytosis rates, superoxide anion production and macrophage viability. By analyzing the kinetics of nitric oxide production, after 4 to 10 hours of cellular culture incubation, there was lower average production of this radical in the MRSA system when compared to MSSA. However, after 12 hours, no differences were detected between both systems. CONCLUSION: It is claimed that methicillin resistance may be a factor that influences the bacteria's ability to escape from macrophage microbicide response. Although the results of some immunological parameters were similar in the surveyed systems, the oscillations occurred during the production of nitric oxide may contribute significantly to the survival of Staphylococcus aureus.